Corporate Governance, Non-Debt Tax Shield, Asset Structure, and Financial Performance with Growth Opportunity - Dienata, Sherly Putri; Maulana, Wahyu (Department of Accounting, Faculty of Economics & Business, 2026)
This study aims to determine the effect of Good Corporate Governance (proxied by the proportion of independent commissioners), Non-Debt Tax Shield, and Asset Structure on Financial Performance, with Growth Opportunity as a mediating variable. The study used secondary data from listed companies and employed the Partial Least Squares (PLS-SEM) method with 50 observations. The results show that Asset Structure is the only variable with a positive and significant effect on Financial Performance, while Good Corporate Governance, Non-Debt Tax Shield, and Growth Opportunity do not. The findings also indicate that Growth Opportunity does not mediate the influence of Good Corporate Governance, Non-Debt Tax Shield, or Asset Structure on Financial Performance. Overall, the study concludes that internal asset composition plays a more dominant role in improving financial performance than governance mechanisms, tax-shield benefits, or growth potential.